Analisis Nilai Tambah dan Kelayakan Usaha Pengelolaan Kopra di Kabupaten Bone, Kecamatan Tellusiattinge, Desa Ulo - Suryani Suryani; Sulfiana Sulfiana; Syamsul Rahman; Helda Ibrahim (Lembaga Pengembangan Kinerja Dosen, 2025)
Processing coconut into copra is an important strategy to increase value added and farmers’ income in rural areas. However, traditional copra processing businesses often face problems such as price fluctuations, high production costs, and limited understanding of business feasibility analysis. This study aims to analyze the value added and business feasibility of copra processing in Bone Regency, specifically in Tellusiattinge District, Ulo Village. The study was conducted from September to October 2025 using a descriptive method with qualitative and quantitative approaches. The research population consisted of 15 copra processing entrepreneurs, all of whom were selected as respondents using a census technique. Data were collected through interviews, observation, and documentation. Data analysis included production cost analysis, income analysis, value added analysis using the Hayami method, and business feasibility analysis using the Revenue Cost Ratio. The results showed that the average value added from processing coconut into copra was Rp2,100 per kilogram with a value added ratio of 37.5 percent, which falls into the medium category. The average Revenue Cost Ratio of 1.35 indicates that the copra processing business is feasible and profitable to operate. The findings imply that copra processing has the potential to increase farmers’ income and rural economic development, therefore requiring support in improving production efficiency and adopting better processing technologies to enhance value added.